2018
DOI: 10.1155/2018/7105872
|View full text |Cite
|
Sign up to set email alerts
|

Model-Free Adaptive Control of Direct Drive Servo Valve of Electromagnetic Linear Actuator

Abstract: An electromagnetic linear actuator (EMLA) has a promising application in direct motion control. However, ELMA will inevitably inherit uncertainties in the face of load changes, system parameter perturbation, and inherent system nonlinearities, all of which constitute disturbances adversely affecting the precision and adaptability of the control system. A model-free adaptive control (MFAC) strategy based on full form dynamic linearization (FFDL) was proposed to reduce the sensitivity of the control system to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The electromagnetic linear actuator system consists of three subsystems, the circuit, the magnetic circuit and the mechanical subsystem. Figure 2 describes the coupling relationship between the sub-systems [19].…”
Section: Structure and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The electromagnetic linear actuator system consists of three subsystems, the circuit, the magnetic circuit and the mechanical subsystem. Figure 2 describes the coupling relationship between the sub-systems [19].…”
Section: Structure and Modelmentioning
confidence: 99%
“…The MFAC control algorithm has strong robustness and can uniformly deal with the control problems of nonlinear systems with time-varying structure, time-varying parameters and time-varying order, and its control performance is little affected by parameter variations, and the PPD as slow time-varying parameters are insensitive to parameter variations and system structure, so that the control system can get good control effects by choosing different parameter values within a certain range. Some of the controller parameters were selected for multi-objective optimization and combined with the [24], The set of parameters obtained after optimization of the MFAC and MFASMC control scheme parameters are: weighting factorµ = 1, λ = 1.2 × 10 −6 , initial value of Φf,Ly,Lu (k) is Φf,Ly,Lu (1) = [0.03, 0.05, 0.03, 0.03] T , step factor ρ 1 = 0.4, ρ 2 = 0.1, ρ 3 = 0.7, ρ 4 = 0.7, ε = 10 −5 . The simulation sampling period is chosen as 0.000 01 s.…”
Section: Control Performance Analysismentioning
confidence: 99%
“…A miniature EMLA with self-alignment and self-attachment features is proposed (Zhi et al , 2020). A model-free self-applicable control strategy with full morphological dynamic linearization was used and the robustness and effectiveness of the algorithm on EMLA were verified (Zhu et al , 2018). Single-discipline optimization often uses a key output as the objective function for optimization, and other outputs are considered as constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In MFAC, dynamic linear time-varying model has three main forms, namely, compact form dynamic linearization, partial form dynamic linearization, and full form dynamic linearization [5]. Partial-form dynamic linearization and full form dynamic linearization have more parameters [5]- [7]; thus, they have more adjustable freedom and controller design flexibility [6]. However, they also substantially increase the complexity and difficulty during the controller design.…”
mentioning
confidence: 99%
“…The linearization model structure of the compact form is simple with a minimum number of controller parameters; hence, the stability and parameter selection of the compact form [5], [8]- [10] are explored in depth, and comparative studies [10], [11] are widely reported. Given that the compact form of the MFAC structure is simple and computation is small, many applications are obtained, such as, multi-agent system and formation control [12], [13], variable polarity plasma arc welding [14], interlinked AC/DC microgrids [15], autonomous cars [16], gas collector pressure system of coke ovens [17], data dropout compensation for networked nonlinear systems network [18], direct drive servo valve of electromagnetic linear actuator, and position sensorless drive for high speed BLDC motors [7], [19]. However, the following problems in the existing MFAC need further examination.…”
mentioning
confidence: 99%